Parents' Perceptions of Subjective Well-Being in Children with ADHD - Iriani Indri Hapsari; Aulia Iskandarsyah; Poeti Joefiani; Juke R. Siregar (Journal of Psychology and Instruction, 2020)
The purpose of this research is to descriptively identify parents’ perception of subjective well-being in children with ADHD. Qualitative research method was performed with a sample of 18 parents (15 mothers, 3 fathers). Data analysis was using thematic analysis. The results of this study indicate that children with ADHD in general, based on the perceptions of parents, show that children with ADHD are generally not wellbeing, but there are those who claim to be well-being and some say that some are sometimes well-being and other times they feel less wellbeing. Children feel wellbeing when their needs are met, they get environmental support, there is no negative stigma. Children feel less well-being because of the lack of acceptance of the child's condition, the existence of a negative stigma, the child still behaves negatively, and their needs are not fulfilled. Parents play a role in helping optimize children's well-being by conditioning the environment, children and parents themselves, and surrendering to God to better suit the needs of children with ADHD.